1989
DOI: 10.1016/s0022-5347(17)40578-7
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin, Cyclophosphamide and Doxorubicin Chemotherapy for Unresectable Urothelial Tumors: The M. D. Anderson Experience

Abstract: We reviewed retrospectively 97 patients treated with cisplatin, cyclophosphamide and doxorubicin chemotherapy at our hospital to evaluate predictive variables for response to chemotherapy and long-term survival free of disease. Histological subtype influenced response: 70 per cent of the patients with pure transitional cell carcinoma achieved an objective response (partial remission 31 per cent and complete remission 39 per cent), whereas 45 per cent of those with mixed tumors achieved response (partial remiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
8

Year Published

1991
1991
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(40 citation statements)
references
References 4 publications
2
30
0
8
Order By: Relevance
“…7 The development of more effective modalities to reduce deaths from localized disease, such as preoperative radiotherapy and adjuvant chemotherapy, may improve the results in transitional cell carcinoma but not in squamous tumors. 6,[38][39][40][41] When considering the progress with orthotopic bladder replacement, like the urethral Kock pouch adopted in five patients in this work, the acceptance of patients for surgical treatment had improved. The current treatment modalities do not alter the dismal prognosis of those unfortunate patients diagnosed with far-advanced disease.…”
Section: Discussionmentioning
confidence: 95%
“…7 The development of more effective modalities to reduce deaths from localized disease, such as preoperative radiotherapy and adjuvant chemotherapy, may improve the results in transitional cell carcinoma but not in squamous tumors. 6,[38][39][40][41] When considering the progress with orthotopic bladder replacement, like the urethral Kock pouch adopted in five patients in this work, the acceptance of patients for surgical treatment had improved. The current treatment modalities do not alter the dismal prognosis of those unfortunate patients diagnosed with far-advanced disease.…”
Section: Discussionmentioning
confidence: 95%
“…While recent studies have found certain variants such as micropapillary and plasmacytoid to act more aggressively, SQD has been historically described to act similarly to NV histology 5,11,14,15,18,19 . However, much of the SQD literature draws on older cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Although SQD was previously shown to be associated with higher pathologic staging and increased risk of local recurrence, when accounting for stage, SQD does not alter overall survival (OS) or disease-specific survival (DSS) 7,8,[11][12][13] . Furthermore, there is evidence suggesting that SQD may be equally sensitive to chemotherapy as non-variant (NV) urothelial bladder cancer 10,12,[14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
“…Cisplatin [cis-dichlorodiamine platinum (II)], a potent antitumor compound, has been used successfully against a number of tumors in animals and human cancers [10][11][12]. This compound has been reported to activate murine peritoneal and bone marrow-derived macrophages to the tumoricidal state [13][14][15], in which state the cells show increased production of interleukin-1 (IL-1) and tumor necrosis factor (TN F) [16], reactive oxygen metabolites [17,18], reactive nitrogen intermediates [19], lysozyme, and arginase [20].…”
Section: Discussionmentioning
confidence: 99%